Introducing the Massachusetts CSI Nursing Delirium Collaborative. Issue 6 (November 2016) - DiLibero, Justin; Edwards, Erica; Hanson, Dave
Abstract : Abstract: In the final installment of this three-part series, the authors reveal how the Boston cohort of the American Association of Critical-Care Nurses Clinical Scene Investigator Academy launched a collaborative to improve patient safety and quality outcomes related to delirium. Abstract : In the final installment of this three-part series, the authors reveal how the Boston CSI Academy launched a collaborative to improve patient safety and quality outcomes related to delirium.